Predicting Tendency Toward Risky Behaviors Based on Emotion Regulation Difficulties and Mentalization in Children of Divorce: The Mediating Role of Post Traumatic Growth and the Moderating Role of Family Communication Patterns - Mohseni Mansour , Seyedeh Nafiseh; Kadkhoda, Nasrin; Khelghati, Bita; Miri , Seyedeh Mahsan; Ranjbar, Mehrnoosh (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to predict tendencies toward risky behaviors based on difficulties in emotion regulation and mentalization in children of divorce, with the mediating role of post traumatic growth and the moderating role of family communication patterns. Methods and Materials: This descriptive–correlational study using path analysis was conducted in 2025. The statistical population consisted of children of divorce aged 15–18 years in Babol, from whom 300 participants were selected through purposive sampling. Data were collected using the Iranian Adolescents Risk Taking Scale (2011), Difficulties in Emotion Regulation Scale (2004), Mentalization Questionnaire (2018), Post Traumatic Growth Inventory (1996), and Family Communication Patterns Questionnaire (1990). Data were analyzed using Pearson correlation coefficients, path analysis, moderation analysis, and bootstrap procedures in SPSS and AMOS. Findings: The results indicated that difficulties in emotion regulation had a significant positive direct effect on risky behavior tendencies (β = 0.41, p < .001), whereas mentalization (β = −0.36, p < .001), post traumatic growth (β = −0.29, p < .001), and family communication patterns (β = −0.31, p < .001) had significant negative direct effects. Furthermore, family communication patterns significantly moderated the relationship between difficulties in emotion regulation and risky behaviors (β = −0.18, p < .001), as well as the relationship between mentalization and risky behaviors (β = −0.15, p < .01). Bootstrap results also confirmed the mediating role of post traumatic growth in the relationship between difficulties in emotion regulation and risky behaviors (β = 0.12, 95% CI [0.06, 0.19]) and between mentalization and risky behaviors (β = −0.12, 95% CI [−0.18, −0.05]). The proposed model demonstrated good fit to the data (CFI = 0.95, TLI = 0.94, RMSEA = 0.054). Conclusion: The findings suggest that children of divorce with greater difficulties in emotion regulation are more likely to engage in risky behaviors, whereas higher levels of mentalization, post traumatic growth, and constructive family communication patterns serve as protective factors.